Juvenile Glyptodont (Mammalia, Cingulata) from the Miocene of Patagonia, Argentina: Insights into Mandibular and Dental Characters. Issue 1 (2nd January 2020) - González Ruiz, Laureano R.; Brandoni, Diego; Zurita, Alfredo E.; Green, Jeremy L.; Novo, Nelson M.; Tauber, Adan A.; Tejedor, Marcelo F.
ABSTRACT: The earliest complete glyptodonts (Glyptodontidae, Cingulata) found belong to the Propalaehoplophorinae from Santa Cruz Formation (late early Miocene, Burdigalian) in Patagonia, Argentina. Although several skulls and mandibles have been described from this formation, and assigned to five genera ( Propalaehoplophorus Ameghino, Cochlops Ameghino, Asterostemma Ameghino, Eucinepeltus Ameghino, and Metopotoxus Ameghino), the fossil record and knowledge of juvenile specimens of glyptodonts are still poor. Here, we provide a detailed morphological description of a mandible of a juvenile propalaehoplophorinae glyptodont from the Santa Cruz Formation, using micro-computed tomography and scanning electron microscopy images. We compare the juvenile mandible with adult specimens and discuss the taxonomic assignment, the juvenile and adult mandibular and dental characters, and dental eruption and tooth wear.